Biochar with large specific surface area recruits N2O-reducing microbes and mitigate N2O emission. (May 2021) - Liao, Jiayuan; Hu, Ang; Zhao, Ziwei; Liu, Xiangrong; Jiang, Chu; Zhang, Zhenhua
Abstract: Bacteria and archaea colonizing on biochar have been reported to possess nitrogen-metabolizing abilities. A larger specific surface area of biochar may enhance the activities of nitrous oxide (N2 O)-reducing microbes, thereby mitigating N2 O emission; however, the underlying mechanisms remain unclear. A 56-day incubation assay was performed with five treatments: no addition, urea only, and addition of three types of biochars (with different specific surface areas: 1193, 2023, and 2773 m 2 g −1 ) combined with urea. N2 O emission increased with the specific surface area of biochar up to 2023 m 2 g −1 and decreased thereafter by 37% as compared with the urea only addition. By increasing soil pH, C/N ratio, nitrogen availability, and cation exchange capacity, the biochar with the largest specific surface area decreased soil N2 O emission by affecting the diversity, abundance, and composition of total bacteria and N2 O-producing microbial communities. A larger specific surface area of biochar correlated with a higher abundance of nitrogen-fixing ( nifH ), -nitrifying ( amoA ), and -denitrifying ( nirK, nirS, and nosZ ) genes. An increased abundance of ammonia-oxidizing bacteria and archaea, in the biochar with a smaller specific surface area, resulted in higher N2 O emission. As the abundance of nosZ increased, the addition of the biochar with the largest specific surface area resulted in a higher ratio of nosZ /( amoA + nirS + nirK ), leading to decreased N2 O emission. Furthermore, the abundance of nifH, amoA, nirK, and nosZ on biochar (extraction from soil after 56-day incubation) was positively correlated with that in soil. Thus, the relative specific surface area of biochar should be taken into consideration when using it in agriculture, as our results show that biochars with larger specific surface areas decrease N2 O emission by recruiting N2 O-reducing microbes and upregulating the abundance of nitrogen-fixing, -nitrifying, and -denitrifying genes. Highlights: A larger biochar surface area decreases soil N2 O emission. Bacteria stimulated by biochar possesses nitrogen-metabolizing activity. N2 O reducing microbes on biochar and in the soil are positively related. nosZ, a functional marker gene, localization on biochar decreases soil N2 O emission.